2020
DOI: 10.1186/s12967-020-02386-w
|View full text |Cite
|
Sign up to set email alerts
|

FTY720 ameliorates GvHD by blocking T lymphocyte migration to target organs and by skin fibrosis inhibition

Abstract: Background: Fibrosis is the formation of excess connective tissue in an organ or tissue during a reparative or reactive process. Graft-versus-host disease (GvHD) is a medical complication of allogeneic tissue transplantation with transplanted donor T cell-mediated inflammatory response; it is characterized by a severe immune response with fibrosis in the final stage of the inflammatory process. T helper 17 cells play a critical role in the pathogenesis of GvHD. Fingolimod (FTY720), an analogue of sphingosine-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…This is in accordance with the more recently defined fourth criteria of GVHD development (20). A variety of molecules have been testing for this effect, notably maraviroc that blocks CCR5 ( Figure 2) (81, 82), fingolimod (FTY720) that mostly interferes with T cells' infiltration into skin (83)(84)(85), and natalizumab that has been shown to mediates homing of lymphocytes to the gastrointestinal tract (86), with promising results.…”
Section: Depletion Of Alloreactive T Cellssupporting
confidence: 75%
“…This is in accordance with the more recently defined fourth criteria of GVHD development (20). A variety of molecules have been testing for this effect, notably maraviroc that blocks CCR5 ( Figure 2) (81, 82), fingolimod (FTY720) that mostly interferes with T cells' infiltration into skin (83)(84)(85), and natalizumab that has been shown to mediates homing of lymphocytes to the gastrointestinal tract (86), with promising results.…”
Section: Depletion Of Alloreactive T Cellssupporting
confidence: 75%
“…Consistent with the results in acute GVHD, treatment with FTY720 early after allo-HCT restores PTEN expression and normalization of Smad3 phosphorylation and diminishes immune cell infiltration into skin, improving sclerodermatous during chronic GVHD ( 58 ). Another study also supports these findings, demonstrating that FTY720 treatment impairs CD4 + T cells differentiation into Th1, Th2, and Th17 and further ameliorates skin fibrosis ( 59 ). Moreover, FTY720 treatment increases IL-10 production in a subset of B cells via S1PR1 ( 57 ) and decreases splenic dendritic cells (CD11c + ) by 50%, contributing to chronic GVHD control ( 58 ).…”
Section: S1p Metabolismmentioning
confidence: 64%
“…To exclude the contribution of circulating memory cells to the recall responses, we administered FTY720 [ 37 , 38 ] (a S1P inhibitor that blocks the egress of T cells from repositioning from secondary lymphoid organs to the tissue). We found that FTY720 treatment followed by a P. aeruginosa XN-1 challenge induced higher survival in immunized mice ( P < 0.0001) but not in unimmunized mice ( Figure 4(a) ).…”
Section: Resultsmentioning
confidence: 99%